1992
DOI: 10.1139/v92-104
|View full text |Cite
|
Sign up to set email alerts
|

Metal-selenolate chemistry: stereochemistry of adamantane-type clusters of formula [(μ-SePh)6(MSePh)4]2− (M = Zn and Cd)

Abstract: . Can. J. Chem. 70, 792 (1992). The structures of three tetramethylammonium salts containing anions of formula [ ( p~e~h ) ( , (~~e~h ) , 1 ' -(M = Zn and Cd) were determined by single crystal X-ray diffraction techniques. The Zn salt crystallizes in different space groups depending upon the solvent combination used in the synthesis. Thus crystals of (MelN), [Zn,(SePh),o], 1, grown from a mixture of methanol, acetopitrile, and acetone are triclinic, space group P 1, with cell dimensions cz = 13.214 (2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 16 publications
1
13
0
2
Order By: Relevance
“…The lower temperature of 10 ] determined by XRD in ref. [139]. Schematic representation showing nanocrystal surface ligation.…”
Section: A Successful Synthesis Of Colloidal Mn 2r :Cdse Nanocrystalsmentioning
confidence: 99%
“…The lower temperature of 10 ] determined by XRD in ref. [139]. Schematic representation showing nanocrystal surface ligation.…”
Section: A Successful Synthesis Of Colloidal Mn 2r :Cdse Nanocrystalsmentioning
confidence: 99%
“…Adamantane-like anions of the general type [(F-EP~),(MX),]~-are well established for a variety of divalent metal centres, especially for E = S and X = SPh-or halide (1)(2)(3)(4)(5). Of particular relevance to the present paper, some anions of this general type are known for each of the zincgroup elements (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 86%
“…Of particular relevance to the present paper, some anions of this general type are known for each of the zincgroup elements (1)(2)(3)(4)(5). The (pSPh),M, cages, where they exist for ~n(11)-H~(II),, provide possible models for the 'Presented in part at the 74th Canadian Chemical Conference, Hamilton, Ontario.…”
Section: Introductionmentioning
confidence: 99%
“…We have noted that the isomer of [(p-SC6H5)6{HgP-(C6H5),),]+ found in the solid state, isomer 111, is that with the smallest number of 1,3-axial, axial phenyl non-bonded interactions. In an earlier study of related Cd and Zn selenolate complex anions (24), we suggested that the skeleton distorts to minimise the unfavourable repulsive interactions between axially disposed substituents. The presence of bulky triphenylphosphine ligands on the Hg atoms apparently magnifies this distortion.…”
Section: The Synthesis Of the Hg Salt [(P-sc6h5)6{hgp(c6h5)3}mentioning
confidence: 94%